Protocol for the TRANSLATE prospective, multicentre, randomised clinical trial of prostate biopsy technique - Bryant, Richard J.; Yamamoto, Hide; Eddy, Ben; Kommu, Sashi; Narahari, Krishna; Omer, Altan; Leslie, Tom; Catto, James W. F.; Rosario, Derek J.; Good, Daniel W.; Gray, Rob; Liew, Matthew P. C.; et al. (BJU international, 2023)
Objectives Primary objectives: to determine whether local anaesthetic transperineal prostate (LATP) biopsy improves the detection of clinically significant prostate cancer (csPCa), defined as International Society of Urological Pathology (ISUP) Grade Group ≥2 disease (i.e., any Gleason pattern 4 disease), compared to transrectal ultrasound‐guided (TRUS) prostate biopsy, in biopsy‐naïve men undergoing biopsy based on suspicion of csPCa. Secondary objectives: to compare (i) infection rates, (ii) health‐related quality of life, (iii) patient‐reported procedure tolerability, (iv) patient‐reported biopsy‐related complications (including bleeding, bruising, pain, loss of erectile function), (v) number of subsequent prostate biopsy procedures required, (vi) cost‐effectiveness, (vii) other histological parameters, and (viii) burden and rate of detection of clinically insignificant PCa (ISUP Grade Group 1 disease) in men undergoing these two types of prostate biopsy. Patients and Methods The TRANSLATE trial is a UK‐wide, multicentre, randomised clinical trial that meets the criteria for level‐one evidence in diagnostic test evaluation. TRANSLATE is investigating whether LATP biopsy leads to a higher rate of detection of csPCa compared to TRUS prostate biopsy. Both biopsies are being performed with an average of 12 systematic cores in six sectors (depending on prostate size), plus three to five target cores per multiparametric/bi‐parametric magnetic resonance imaging lesion. LATP biopsy is performed using an ultrasound probe‐mounted needle‐guidance device (either the ‘Precision‐Point’ or BK UA1232 system). TRUS biopsy is performed according to each hospital's standard practice. The study is 90% powered to detect a 10% difference (LATP biopsy hypothesised at 55% detection rate for csPCa vs 45% for TRUS biopsy). A total of 1042 biopsy‐naïve men referred with suspected PCa need to be recruited. Conclusions This trial will provide robust prospective data to determine the diagnostic ability of LATP biopsy vs TRUS biopsy in the primary diagnostic setting.